Multi-network gel composite film fluorescence enhanced substrate as well as preparation method and application thereof
By growing precious metal particles in situ in a multi-network gel to form a multi-gel network-precious metal particle composite film, the problems of uneven distribution and aggregation of precious metal particles in the prior art are solved, and effective enhancement of fluorescence signals and improvement of detection sensitivity are achieved.
Patent Information
- Application Number
- CN202411926868.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-25
AI Technical Summary
The prior art is difficult to form uniform and stable large-size precious metal particles, resulting in poor fluorescence signal enhancement effect, limited detection sensitivity, and the aggregation of precious metal particles and the random plasmon resonance phenomenon affect the repetition and quantitativeness of the detection.
By growing precious metal particles in situ in a multi-network gel with adhesion and reducing properties, a multi-gel network-precious metal particle composite film is formed, the particle size/distribution/gap/density is regulated, aggregation is avoided, and the fluorescence intensity of biofluorescent molecules is enhanced.
The uniform distribution and stability of precious metal particles are achieved, the fluorescence signal is enhanced, the detection sensitivity and repeatability are improved, and the formation of coffee rings and detection deviations are avoided.
Smart Images

Figure HDA0005209451050000011 
Figure HDA0005209451050000012 
Figure HDA0005209451050000021
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of analytical chemistry, and in particular to a multi-network gel composite membrane fluorescence enhancement substrate and a preparation method and application thereof. Background Art
[0002] Compared with detection technologies based on electricity, magnetism, mechanics, etc., optical detection technology based on fluorescence labeling has incomparable advantages in detection in the fields of biology, chemistry, clinical medicine, etc. It can detect targets (small molecules, nucleic acids, proteins, cells, etc.) in samples simply, quickly, reliably, and without radioactive contamination. However, when the concentration of the target marker is low, the fluorescence signal is usually very weak and easily interfered by the fluorescence background of biological molecules in complex background samples, which limits the sensitivity of the detection. Enhancing the fluorescence signal intensity of the target labeled with fluorescent signal molecules is an effective method to improve the sensitivity of target markers and is the key to achieving ultra-sensitive and high-reliability detection of target markers at polar concentrations.
[0003] At present, the intensity of the target marker fluorescence signal is mainly enhanced by precious metal nanoparticles such as gold and silver, which are used to form surface plasmon resonance under the irradiation of excitation light in a specific wavelength range, so that the local electromagnetic field intensity and optical state density increase to enhance fluorescence. The mutual matching between the fluorescent molecules to be tested and the electromagnetic field enhancement area is the key to improving the detection sensitivity. The degree of matching depends on many factors such as the size of the precious metal nanoparticles, the stacking method, and the distance between the fluorescent molecules. Existing studies have shown that large-sized, uniformly densely arranged precious metal particles can solve the problem of difficult matching between the fluorescent molecules to be tested and the electromagnetic field enhancement area. Surface adsorption, chemical self-assembly or thermal annealing effects are usually used to form precious metal substrates, but it is difficult to form uniform and stable large-sized precious metal particles. They all lack structural gap hotspots and effective regulation mechanisms for particle gaps. The plasmon resonance phenomenon generated by the formed substrate is relatively random, the adsorption of fluorescent biological molecules to be tested is limited and difficult to be evenly distributed, the repeatability is poor, and it is difficult to use for quantitative analysis.
[0004] At present, physical methods for generating precious metal particles, such as laser ablation, mechanical ball milling, evaporation condensation, high-pressure magnetron sputtering, etc., although the generated particles are stable and of high purity, the process is too expensive, complicated, time-consuming and has high requirements for preparation equipment, making it difficult to achieve dense arrangement of the required structure and efficient and low-cost batch preparation; chemical methods such as liquid phase reduction, photochemical method, microemulsion method, hydrothermal method, etc., although the generated particles have good dispersion, simple operation and low equipment requirements, it is difficult to effectively fix a large area on the detection substrate and stabilize it in the detection system. In addition, the particles generated by existing physical and chemical methods are prone to agglomeration, which in turn affects the matching effect between the fluorescent molecules to be detected and the electromagnetic field enhancement area, making the detection difficult to repeat and quantify, and difficult to meet application requirements. Summary of the invention
[0005] The present invention aims to solve at least one of the above technical problems existing in the prior art. To this end, the purpose of the present invention is to provide a multi-network gel composite film fluorescence enhancement substrate and a preparation method and application thereof.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] The first aspect of the present invention provides a fluorescence enhancement substrate, comprising: a multi-gel network-noble metal particle composite film, wherein the multi-gel network-noble metal particle composite film comprises:
[0008] an adhesive first gel network formed by cross-linking an adhesive polymer;
[0009] A reducing second gel network is formed by cross-linking of reducing natural polymers;
[0010] A third gel network containing noble metal particles, formed by in-situ growth of noble metal particles on the adhesive first gel network;
[0011] The fourth gel network containing precious metal particles is formed by in-situ growth of precious metal particles in the reducing second gel network.
[0012] In the present invention, the enhanced fluorescence noble metal particles are grown in situ in a multi-network gel with adhesiveness and reducibility, which not only makes it easier to control the size / distribution / gap / density of the noble metal particles and avoid aggregation of the noble metal particles, but also enables better binding with the substrate and enhances the fluorescence intensity of the bioluminescent molecules, but also has certain target enrichment characteristics and can prevent uneven diffusion of the sample solution to form coffee rings, thereby improving the sensitivity of detection and avoiding detection deviations caused by coffee rings.
[0013] In some embodiments of the present invention, in the multi-gel network-precious metal particle composite film, the mass ratio of precious metal particles, adhesive polymer and reducing natural polymer is 0.15-7:10-60:0.5-4; such as 0.15-5.5:10-60:0.5-4.
[0014] In some embodiments of the present invention, the reductive second gel network is formed by a reductive natural polymer and a second crosslinking agent; the second crosslinking agent includes at least one of a metal ion salt, a polyphenol crosslinking agent, and an aldehyde crosslinking agent, such as at least one of calcium chloride, magnesium chloride, aluminum chloride, ferric chloride, sodium hydroxide, potassium hydroxide, calcium hydroxide, dopamine, tannic acid, genipin, glutaraldehyde, and acetaldehyde; the mass ratio of the reductive natural polymer to the second crosslinking agent is 0.1 to 10: 0.5 to 4. The second crosslinking agent can strengthen the crosslinking strength of the reductive second gel network and occupy the ion sites vacated in the crosslinked network after the noble metal ions are reduced to particles.
[0015] In some embodiments of the present invention, the adhesive polymer includes at least one of polyacrylamide, fibrin, cyanoacrylate, chitosan, natural polysaccharide, and polyurethane. Such polymers can provide good adhesion and have strong adsorption properties for substrates, noble metal particles, and biomolecules.
[0016] In some embodiments of the present invention, the reducing natural polymer includes at least one of hyaluronic acid (HA), methacrylated gelatin (GelMa), sodium alginate (SA), natural polysaccharides, and chitosan; this type of natural polymer has strong reducing properties and can form complexes with precious metal cations to reduce them to precious metal particles.
[0017] In some embodiments of the present invention, the precious metal particles include at least one of nano-gold, nano-silver, nano-copper, and nano-platinum; the average particle size of the precious metal particles is 20 to 200 nm; and the ultraviolet absorption range of the precious metal particles is 300 to 600 nm.
[0018] In some embodiments of the present invention, the thickness of the multi-gel network-noble metal particle composite film is 0.04 μm to 1.0 mm, such as 0.5 μm to 0.8 mm, 0.8 μm to 0.6 mm, 1.0 μm to 0.5 mm.
[0019] In some embodiments of the present invention, the fluorescence enhancing substrate also includes a substrate layer, and the multi-gel network-noble metal particle composite film is attached to the substrate layer; the material of the substrate layer includes any one of glass, polymethyl methacrylate (PMMA), polyethylene terephthalate (PET), polystyrene (PS), and medical tape; the thickness of the substrate layer is 1.5 to 2.5 mm.
[0020] In some embodiments of the present invention, the fluorescence enhancing substrate also includes an isolation layer, and the isolation layer is arranged on the multi-gel network-noble metal particle composite membrane; the isolation layer is arranged on the multi-gel network-noble metal particle composite membrane by physical adsorption and / or chemical bonds; the isolation layer includes a single layer, two layers or multiple layers, and the material of the isolation layer includes at least one of anionic polyelectrolyte, cationic polyelectrolyte, and semiconductor medium; the material of the isolation layer includes polyethyleneimine (PEI), polystyrene sulfonate (PSS), polydimethylammonium chloride (PDADMAC), sodium alginate (SA), hyaluronic acid (HA), and silica; the thickness of the isolation layer is 5 to 25 nm.
[0021] The second aspect of the present invention provides a method for preparing the fluorescence enhancement substrate, comprising the following steps:
[0022] The mixed solution of adhesive polymer and reducing natural polymer is cross-linked and solidified, and then placed in a solution containing noble metal ions for reaction, and the multi-gel network-noble metal particle composite film is obtained after photochemical reduction.
[0023] In some embodiments of the present invention, the method for preparing the fluorescence enhancing substrate comprises the following steps: cross-linking and curing a mixed solution of an adhesive polymer and a reducing natural polymer, then placing it in a solution containing precious metal ions for reaction, and placing it in an ionic salt solution for cross-linking and encapsulation after photochemical reduction to obtain the multi-gel network-precious metal particle composite film.
[0024] In some embodiments of the present invention, the method for preparing the fluorescence enhancing substrate comprises the following steps: placing a mixed solution of an adhesive polymer and a reducing natural polymer on a substrate layer for cross-linking and curing, then placing it in a solution containing precious metal ions for reaction, and then photochemically reducing it; and optionally placing it in an ionic salt solution for cross-linking and encapsulation to obtain the fluorescence enhancing substrate.
[0025] In some embodiments of the present invention, the mixed solution further includes a first crosslinking agent and a photoinitiator, wherein the first crosslinking agent includes at least one of N-hydroxymethyl acrylamide, N-hydroxy acrylamide, N,N-methylenebisacrylamide (Bis), and N,N'-methylenebisacrylamide (MBA); the photoinitiator includes at least one of phenyl (2,4,6-trimethylbenzoyl) lithium phosphate (LAP), 1-hydroxycyclohexyl phenyl ketone (UV-184), and 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylbenzoyl benzoyl (I2959); the first crosslinking agent and the adhesive polymer undergo a crosslinking reaction to form an adhesive first gel network; the mass concentration ratio of the first crosslinking agent, the photoinitiator, and the adhesive polymer is 0.15-0.75: 0.1-0.5: 10-60. The temperature of the crosslinking reaction is 10-60°C and the time is 10-120s.
[0026] In some embodiments of the present invention, the mixed solution further includes a second crosslinking agent, which includes a metal ion salt, such as at least one of calcium chloride, magnesium chloride, aluminum chloride, and ferric chloride; the second crosslinking agent and the reducing natural polymer undergo a crosslinking reaction to form a reducing second gel network; the mass concentration ratio of the second crosslinking agent to the reducing natural polymer is 0.1 to 10: 0.5 to 4, such as 0.5 to 2: 0.5 to 4. The temperature of the crosslinking reaction is 10 to 60°C, and the time is 60 to 600s.
[0027] In some embodiments of the present invention, in the mixed solution, the mass concentration of the adhesive polymer is 10% to 60%; the mass concentration of the reducing natural polymer is 0.15% to 7%, such as 0.5% to 4%.
[0028] In some embodiments of the present invention, in the solution containing precious metal ions, the mass concentration of precious metal ions is 0.5% to 2%.
[0029] In some embodiments of the present invention, the mass concentration of the ionic salt solution is 0.1% to 10%, such as 0.1% to 5%.
[0030] In some embodiments of the present invention, the photochemical reduction comprises ultraviolet light curing, and the ultraviolet light intensity is 70 μW / cm 2 ~1200mW / cm 2 The irradiation time is 10s~1000s, such as 20s~800s, 30s~600s, 50s, 80s, 100s, 120s, 200s, 300s, 400s, 500s, etc.
[0031] In some embodiments of the present invention, the method for preparing the fluorescence enhancing substrate further includes placing the multi-gel network-noble metal particle composite membrane in a material solution of an isolation layer, physically adsorbing and / or chemically cross-linking to form an isolation layer, and optionally placing it in an ionic salt solution for cross-linking and encapsulation to obtain the fluorescence enhancing substrate.
[0032] The third aspect of the present invention provides a microfluidic fluorescence detection chip, comprising the fluorescence enhancement substrate and a structural cover.
[0033] In some embodiments of the present invention, the fluorescence enhancement substrate is bonded to a structural cover sheet.
[0034] In some embodiments of the present invention, the material of the structural cover sheet includes at least one of polydimethylsiloxane (PDMS), polymethyl methacrylate (PMMA), polyethylene terephthalate (PET), and polystyrene (PS).
[0035] The fourth aspect of the present invention provides a method for detecting target concentration, including using the microfluidic fluorescence detection chip for detection.
[0036] In some embodiments of the present invention, the detection method includes contacting the target to be detected with the fluorescence enhancement substrate for detection.
[0037] In some embodiments of the present invention, the detection method includes performing fluorescence intensity detection, obtaining fluorescence intensity, and determining target concentration.
[0038] The fifth aspect of the present invention proposes the use of the fluorescence enhancement substrate in detecting target concentration.
[0039] In some embodiments of the present invention, the target includes at least one of a small molecule, a nucleic acid, a protein, and a cell.
[0040] In some embodiments of the present invention, the detection method comprises at least one of an immunosandwich method, an immunofluorescence decay method, and an adsorption method.
[0041] The beneficial effects of the present invention are:
[0042] The present invention will enhance the in-situ growth of fluorescent noble metal particles in a multi-network gel with high adhesion and high reducibility. It is not only easier to control the size / distribution / gap / density of the noble metal particles, avoid aggregation of the noble metal particles, and better combine with the substrate, but also has certain fluorescence enhancement characteristics, target enrichment characteristics and prevents uneven diffusion of the sample solution to form coffee rings, thereby improving the sensitivity of detection and avoiding detection deviations caused by coffee rings.
[0043] The preparation process of the fluorescence-enhanced substrate of the present invention is relatively simple and does not rely on expensive equipment and processes. It can simply and quickly form a multi-network gel-noble metal composite film with fluorescence-enhanced properties on the substrate in batches, providing an effective solution for the highly sensitive, rapid, wide linear, and standardized detection of biological molecules at polar concentrations. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 This is a physical picture of the chip prepared in Example 4 of the present invention.
[0045] Figure 2 The violet light absorption spectra of the fluorescence enhanced substrate obtained under different irradiation times in Example 1 of the present invention.
[0046] Figure 3 This is the violet light absorption spectrum at different positions of the fluorescence enhancement substrate prepared in Example 4 of the present invention.
[0047] Figure 4 The violet light absorption spectra of the substrate obtained under different irradiation times in Comparative Example 1 of the present invention.
[0048] Figure 5 This is a linear relationship diagram of the detection chip of the fluorescence enhanced substrate in Example 4 of the present invention used for CEA-Fitc detection.
[0049] Figure 6 The fluorescence intensity is detected at the center and edge of the fluorescence enhancement substrate in Example 4 of the present invention.
[0050] Figure 7 This is the enhancement effect of the liquid system in Comparative Example 4 of the present invention. DETAILED DESCRIPTION
[0051] The present invention is further described in detail below by specific examples. Unless otherwise specified, the raw materials, reagents or devices used in the examples and comparative examples can be obtained from conventional commercial sources or can be obtained by prior art methods. Unless otherwise specified, the experiments or test methods are conventional methods in the art.
[0052] Example 1
[0053] This example prepares a solid multi-network gel composite film fluorescence enhancement substrate, and the specific process is as follows:
[0054] 0.5 mL of a mixed solution of sodium alginate (1 wt%), acrylamide (30 wt%), BIS (0.15 wt%), and LAP (1 wt%) was evenly coated on a round glass slide (55 mm diameter; 1.1 mm thickness) and illuminated with ultraviolet light (405 nm, 1200 mW / cm 2 ) for 10 s, and then immersed in 10 mL of silver nitrate solution (0.5 wt %) for 5 min to form alginate silver complex gel. 2 ) for 30s, 120s, 300s and 600s, washed with deionized water, and then cross-linked with 10mL of 1wt% calcium chloride for 5min, washed with deionized water, and then dried in an oven at 55°C to obtain a fluorescence enhancement substrate with a thickness of 1.16mm; among them, the solid multi-network gel composite membrane fluorescence enhancement membrane has a thickness of 60μm.
[0055] Example 2
[0056] This embodiment prepares a solid multi-network gel composite membrane fluorescence enhancement basement membrane, and the specific process is as follows:
[0057] 0.8 mL of a mixed solution of sodium alginate (1 wt%), acrylamide (30 wt%), BIS (0.15 wt%), and LAP (1 wt%) was evenly coated on a round glass slide (55 mm diameter; 1.1 mm thickness) and exposed to ultraviolet light (405 nm, 1200 mW / cm 2 ) for 10 s, and then immersed in 10 mL of silver nitrate solution (0.5%) for 5 min to form a multi-network gel containing noble metal ions. 2 ) for 300s, washed with deionized water, and then cross-linked with 10mL of 1wt% calcium chloride for 5min, washed with deionized water, and then dried in an oven at 55°C to obtain a fluorescence enhancement substrate with a thickness of 1.20mm; among them, the solid multi-network gel composite membrane fluorescence enhancement membrane has a thickness of 100μm.
[0058] Example 3
[0059] This example prepares a transparent thin sheet multi-network gel composite film fluorescence enhancement substrate, and the specific process is as follows:
[0060] 0.5 mL of a mixed solution of sodium alginate (1 wt%), acrylamide (60 wt%), BIS (0.25 wt%), and LAP (2 wt%) was evenly coated on a round glass slide (55 mm diameter; 1.1 mm thickness) and exposed to ultraviolet light (405 nm, 1200 mW / cm 2 ) for 10 s, and then immersed in 10 mL of silver nitrate solution (0.5 wt%) for 5 min to form a multi-network gel containing noble metal ions. 2 ) for 300s, washed with deionized water, and then cross-linked with 10mL of 1wt% calcium chloride for 5min, washed with deionized water, and then dried in an oven at 55°C to obtain a fluorescence enhancing substrate, forming a transparent thin sheet multi-network gel composite membrane fluorescence enhancing membrane with a thickness of about 160μm.
[0061] Comparative Example 1
[0062] This comparative example prepares a solid calcium alginate film substrate, and the specific process is as follows:
[0063] 0.5 mL of sodium alginate solution (1 wt%) was evenly coated on a round glass sheet (55 mm diameter; 1.1 mm thick), and then immersed in 10 mL of silver nitrate solution (0.5 wt%) to form alginate-silver complex gel. 2 ) for 30s, 120s, 300s and 600s, washed with deionized water, and then cross-linked with 10mL of 1wt% calcium chloride for 5min, then washed with deionized water, and then dried in an oven at 55°C to obtain a solid calcium alginate film fluorescence enhancement substrate.
[0064] Comparative Example 2
[0065] This comparative example prepared a polyacrylamide substrate, and the specific process was as follows:
[0066] 0.5 mL of acrylamide (30 wt%), BIS (0.15 wt%), and LAP (1 wt%) were mixed and applied to a round glass sheet (55 mm in diameter; 1.1 mm thick). It was found that the mixed solution could not be evenly applied to the glass due to its thin viscosity.
[0067] Example 4
[0068] This embodiment prepares a chip, and the specific process is as follows:
[0069] S1: Prepare PDMS solution in a quantitative ratio of 1:100, mix well and stir to remove bubbles in vacuum, pour into a porous mold (2 inches), and bake in a 75°C oven. After molding, cut to obtain a 2-inch circular multi-test hole structure cover sheet (8 test holes on each cover sheet, each test hole has a diameter of 2.54 mm, the same as the diameter and spacing of a 96-well plate hole).
[0070] S2: The fluorescence enhancement substrate and the cover sheet with multiple test holes prepared by ultraviolet irradiation for 300 seconds in Example 1 are bonded together by plasma treatment, and then placed in an oven at 75° C. for 2 hours to prepare a chip.
[0071] The actual chip picture is as follows Figure 1 shown.
[0072] Test example
[0073] This test example tests the ultraviolet absorption intensity of the substrate, and the specific process is as follows:
[0074] The ultraviolet absorption spectra of the substrates in Example 1 and Comparative Example 1 were tested in the range of 350nm to 800nm using an ELISA instrument. The results are as follows: Figure 2 , Figure 3 , Figure 4 shown.
[0075] from Figure 2 It can be seen that with the increase of UV treatment time, the absorption peaks of the substrate in Example 1 are at 390nm, 430nm, 470nm and 500nm, respectively, and the absorbance peak value gradually increases, and the size of the precious metal nanoparticles on the multi-network gel composite film fluorescence enhancement substrate is adjustable.
[0076] As the volume of the mixed solution coated on the circular glass sheet increases, after UV treatment for 300s, the thickness of the base film in Example 2 is 100 μm, which is greater than the thickness of the base film in Example 1 of 60 μm. The thickness of the fluorescence enhanced base of the multi-network gel composite membrane is adjustable.
[0077] from Figure 3 It can be seen that different positions on the substrate are tested (refer to Figure 1 When the sample was taken at five positions 1, 2, 3, 4, and 5 in the sample, and the UV treatment was performed for 300s, the absorption peaks of the substrates in Example 1 were all around 480nm, and the absorbance peaks were all around 1.75, and the absorbance peaks were higher than those in Example 1. The density of the precious metal nanoparticles on the multi-network gel composite membrane fluorescence enhanced substrate was adjustable and the distribution was controllable.
[0078] from Figure 4It can be seen that with the increase of UV treatment time, the substrate absorption peaks of Comparative Example 1 are at 416nm, 430nm, 455nm and 460nm respectively, the size of the generated silver nanoparticles is limited, and the absorbance peak value gradually increases, but the absorbance peak value is much lower than that of Example 1 and Example 3.
[0079] Example 5
[0080] This example uses the chip prepared in Example 4 to test FITC-labeled carcinoembryonic antigen and FITC-labeled neuron-specific enolase (NES-FITC), and the specific process is as follows:
[0081] 60 μL of 0-500 ng / mL fluorescent molecule FITC-labeled lung cancer tumor marker carcinoembryonic antigen (CEA-FITC) solution (0, 0.78, 1.56, 3.125, 6.25, 12.5, 25, 50, 500 ng / mL) were added to the test wells of the test chip, and the linear relationship between the target molecule on the substrate and the fluorescence intensity was obtained by using an ELISA reader under 465 nm excitation light and 535 nm emission light. The results are as follows: Figure 5 shown.
[0082] 60 μL of 125 ng / mL fluorescent molecule FITC labeled lung cancer tumor marker neuron-specific enolase (NES-FITC) solution was added to the test well of the test chip. The center point test and the edge four-point test were selected by the microplate reader under 465 nm excitation light and 535 nm emission light to obtain the NES-FITC fluorescence intensity at the center and edge positions of the same test well on the substrate. The results are as follows: Figure 6 shown.
[0083] from Figure 5 It can be seen that CEA-FITC shows a good linear relationship in the range of 0 to 500 ng / mL on the substrate, and the linearity is also good in the low concentration range of CEA-FITC. 2 =0.998, and the detection limit is less than 0.78 ng / mL.
[0084] from Figure 6 It can be seen that the fluorescence intensity difference between the center and edge positions of 125 ng / mL NES-FITC on the substrate is small, and the constructed substrate can avoid the detection deviation caused by coffee rings.
[0085] Comparative Example 3
[0086] 60 μL of 125 ng / mL concentration fluorescent molecule FITC-labeled lung cancer tumor marker carcinoembryonic antigen (CEA-FITC) solution and 60 μL of PBS were respectively added into the test wells of the control test chip (multi-test well structure cover + substrate-free glass), and the fluorescence intensity of the target molecule on the control test chip was obtained by an ELISA instrument under 465 nm excitation light and 535 nm emission light.
[0087] The test found that after removing the background (fluorescence intensity of 60μL PBS), the fluorescence intensity of 125ng / mL CEA-FITC on the substrate was much higher than that of the unenhanced substrate. The fluorescence intensity of CEA-FITC on the substrate was enhanced by 4.2 times. The multi-network gel composite membrane fluorescence enhancement substrate has good fluorescence enhancement properties.
[0088] Comparative Example 4
[0089] This comparative example tests the enhancement effect of the liquid system, and the specific process is as follows:
[0090] 0.1 mg / mL of nanosilver with UV absorption of about 480 nm was uniformly mixed with 2 wt% sodium alginate solution, and then CEA-FITC solution was added to prepare a 0-500 ng / mL CEA-FITC gradient concentration solution (0, 0.78, 1.56, 3.125, 6.25, 12.5, 25, 50, 500 ng / mL) containing 0.05 mg / mL nanosilver and 1% sodium alginate. Then 100 μL of 0-500 ng / mL CEA-FITC solution of different concentrations was taken out in a 96-well plate, and the fluorescence intensity of the solution under 465 nm excitation light and 535 nm emission light was tested with an ELISA instrument to analyze the linear relationship between the target molecule concentration and the fluorescence intensity. The results are as follows: Figure 7 shown.
[0091] from Figure 7 It can be seen that CEA-FITC is not linear at low concentrations of 0 to 50 ng / mL.
[0092] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A fluorescence enhancement substrate, characterized in that: include: A multi-gel network-noble metal particle composite membrane, wherein the multi-gel network-noble metal particle composite membrane comprises: an adhesive first gel network formed by cross-linking an adhesive polymer; A reducing second gel network is formed by cross-linking of reducing natural polymers; A third gel network containing noble metal particles, formed by in-situ growth of noble metal particles on the adhesive first gel network; The fourth gel network containing precious metal particles is formed by in-situ growth of precious metal particles in the reducing second gel network.
2. The fluorescence enhancement substrate according to claim 1, characterized in that: In the multi-gel network-noble metal particle composite film, the mass ratio of the noble metal particles, the adhesive polymer and the reducing natural polymer is 0.15-7:10-60:0.5-4.
3. The fluorescence enhancement substrate according to claim 1, characterized in that: The reducing second gel network is formed by cross-linking reducing natural polymers and a second cross-linking agent; the second cross-linking agent includes at least one of metal ion salts, polyphenol cross-linking agents, and aldehyde cross-linking agents.
4. The fluorescence enhancement substrate according to claim 1, characterized in that: The adhesive polymer includes at least one of polyacrylamide, fibrin, cyanoacrylate, chitosan, natural polysaccharide, and polyurethane.
5. The fluorescence enhancement substrate according to claim 1, characterized in that: The reducing natural polymer includes at least one of hyaluronic acid, methacrylated gelatin, sodium alginate, natural polysaccharide and chitosan; and / or the noble metal particles include at least one of nano-gold, nano-silver, nano-copper and nano-platinum.
6. The fluorescence enhancement substrate according to claim 1, characterized in that: The fluorescence enhancement substrate also includes a substrate layer, and the multi-gel network-noble metal particle composite film is attached to the substrate layer.
7. The fluorescence enhancement substrate according to claim 1, characterized in that: The fluorescence enhancement substrate further comprises an isolation layer, and the isolation layer is arranged on the multi-gel network-noble metal particle composite film.
8. A method for preparing the fluorescence enhancement substrate according to any one of claims 1 to 7, comprising the following steps: The mixed solution of adhesive polymer and reducing natural polymer is cross-linked and solidified, and then placed in a solution containing noble metal ions for reaction, and the multi-gel network-noble metal particle composite film is obtained after photochemical reduction.
9. A microfluidic fluorescence detection chip, comprising the fluorescence enhancement substrate and the structural cover sheet according to any one of claims 1 to 7.
10. Use of the fluorescence enhancement substrate according to any one of claims 1 to 7 in detecting target concentration.
Citation Information
Patent Citations
Method for preparing composite nano-silver film for DNA fluorescence detection
CN104089934A
High-strength fluorescent hydrogel and preparation method thereof
CN105504364A
Dual-catalyzed luminol electrochemical luminescence biosensor based on gold nano-particles and titanium dioxide MXenes
CN109490284A
Composite hydrogel coating for monitoring and treating urinary tract infection as well as preparation method and application of composite hydrogel coating
CN114159627A
Preparation method of novel single platinum nanoparticle peroxide detection hydrogel
CN115282889A